Examining the key factors influencing the sustainability of domestic wastewater reuse in Jakarta using AHP method - Theresia, Eliza Sinta; Purwana, Rachmadhi; Rahmatika, Iftita (Universitas Mercu Buana, 2025)
Population expansion, urbanization, economic development, pollution, and climate change are all contributing factors to the growing global problem of water shortage. The Sustainable Development Goals (SDGs) are in danger of being achieved because of this dilemma, particularly SDGs 6 and 11 on clean water and sanitation and sustainable cities, respectively. Only 65.9% of Jakarta's population has access to potable water, and water stress levels range from 40 to 80%. The government is planning a wastewater treatment system (SPALD-T) to recycle household wastewater and produce clean water in order to address this issue. TB. Simatupang's Water Treatment Plant (WWTP) still faces obstacles in adopting wastewater reuse, nonetheless. In Indonesia, wastewater recycling has received little attention, with the majority of studies concentrating on technical concerns rather than sustainability considerations. In contrast, technologies such as desalination and rainfall harvesting are being investigated worldwide. The objective of this research is to examine the technical and non-technical elements that affect wastewater recycling's effectiveness for the generation of sustainable clean water. The results will offer crucial information to help Perumda Paljaya create policies that will effectively utilize wastewater, which will help Jakarta accomplish its sustainable development goals more broadly.